The Synthesis and Herbicidal Activity of 1-Alkyl-3-(Î±-hydroxysubstituted benzylidene)pyrrolidine-2,4-diones - Hua-Zheng Yang (Molecules, 2005)
In the search for better herbicides a series of 1-alkyl-3-(Î±-hydroxy-(un)substituted benzylidene)pyrrolidine-2,4-diones were prepared and their structure-activity relationships studied. All their structures have been confirmed by 1H-NMR andelemental analysis. The preliminary bioassay results indicated that some of them have highherbicidal activity against annual dicotyledonous and monocotyledonous plants.